CUSTOMER SATISFACTION AS A MEDIATOR OF PRICE AND SERVICE QUALITY IN SPA'S CUSTOMERS BRAND SWITCHING BEHAVIOR - Zulhijja, Laila; Surachman, Surachman; Sunaryo, Sunaryo (Jurnal Aplikasi Manajemen, 2023)
This research aimed to identify the effects of customer satisfaction role as mediation of price and service quality to the brand switching on customers of Balqis Spa in Kediri. The research design was explanatory research. The total sample was about 130 respondents through the non-probability sampling method. The method of data collection was a questionnaire. In contrast, the data analysis methods in this research were descriptive analysis and inferential analysis through Partial Least Square (PLS) by exerting the Smart PLS 3.0 version, which aimed to examine the effects simultaneously and the partial effects among variables. The research findings show that the price directly affects the service quality and could directly and significantly affect brand switching. Customer satisfaction could fully mediate the relationship between price and brand switching. Moreover, customer satisfaction could partially mediate between the quality and brand switching for customers of Balqis Spa in Kediri. The future researcher can consider other variables outside the object in this study to increase the accuracy of the model that will be formed.